Pengetahuan, sikap tentang ASI (Air Susu Ibu) dan keterampilan suami ibu nifas dalam melakukan metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin, dan Sugestif) - Nanda Wilda Lestari; Susmiati Susmiati; Lili Fajria (Holistik Jurnal Kesehatan, 2020)
Knowledge, attitudes about  breast milk and skills of the husbands of postpartum mothers in the SPEOS method Background: Breastfeeding is a natural process for a mother to support and prosper her child after childbirth. The husband's role by providing support to breastfeeding mothers affects the success of breastfeeding.Purpose: To know the knowledge, attitudes about breast milk and the skills of the postpartum husband in performing the SPEOS method (Endorphin, Oxytocin and Suggestive Massage Stimulation)Method: Quantitative research with the research design "Quasy Experimental Pre-Post Test With Control Group". The research population was the husbands of the postpartum mothers at Andalas public health centre Padang. The sampling technique used random sampling techniques and obtained a sample of 34 respondent. The research instrument used a questionnaire.Results: Showed that the knowledge, attitudes, and skills of the husbands of postpartum mothers increased after being given health education about breast milk and the SPEOS method (Endorphin, Oxytocin and Suggestive Massage Stimulation).Conclusion: Health education about breast milk and the SPEOS method (Endorphin, Oxytocin and Suggestive Massage Stimulation) affect the knowledge, attitudes and skills of husbands.Keywords: Breast milk; SPEOS method; Knowledge; Attitudes; Skills; HusbandPendahuluan: Menyusui adalah proses alami bagi seseorang ibu untuk menghidupi dan mensejahterakan anak pasca melahirkan, peran suami dengan memberikan dukungan pada ibu menyusui mempengaruhi keberhasilan dalam menyusui.Tujuan: Diketahui pengetahuan, sikap tentang ASI (Air Susu Ibu) dan keterampilan suami ibu nifas dalam melakukan metode SPEOS (Stimullasi Pijat Endorphin, Oksitosin dan Sugestif)Metode: Penelitian kuantitatif dengan desain penelitian “Quasy Experimental Pre-Post Test With Control Group”. Populasi penelitian adalah suami ibu nifas di Puskesmas Andalas Padang. Teknik pengambilan Sampel menggunakan teknik random sampling dan didapatkan sampel berjumlah 34 responden. Instrumen penelitian menggunakan kuisioner.Hasil: Menunjukkan bahwa pengetahuan, sikap, dan keterampilan suami ibu nifas meningkat setelah diberikan pendidikan kesehatan tentang ASI (Air Susu Ibu) dan metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin dan Sugestif).Simpulan: Pendidikan kesehatan tentang ASI (Air Susu Ibu) dan metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin dan Sugestif) berpengaruh terhadap pengetahuan, sikap dan keterampilan suami.